2001
DOI: 10.1590/s0103-90162001000100008
|View full text |Cite
|
Sign up to set email alerts
|

Estresse hídrico e reguladores de crescimento na germinação de sementes de canafístula

Abstract: RESUMO: Sementes selecionadas escarificadas de canafístula foram submetidas a estresses hídricos simulados, sob 27°C, com ou sem a adição de poliaminas e giberelina. Os valores de porcentagem e velocidade de germinação obtidos com os testes realizados indicaram que as sementes são resistentes ao estresse hídrico, e a adição de putrescina e espermidina nas concentrações de 5 e 10mM aumenta a performance sob estresse hídrico. O uso de giberelina permite a ampliação do limite máximo de tolerância ao estresse hídr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 14 publications
1
8
0
6
Order By: Relevance
“…Still with Passifl ora alata, Ferreira (1998) observed that GA 3 at 100 mg L -1 promoted better germination, while with Passifl ora nitida Passos et al (2004) reported that for in vitro germination the most suitable gibberellic acid concentration was 1000 mg L -1 , with or without luminosity. Botelho and Perez (2001) reported signifi cant effects on the germination percentage and speed with seeds of Peltophorum dubium Spreng (Taubert). With seeds of Jatropha elliptica, Añez et al (2006) found higher germination percentages in treatments using gibberellic acid at concentrations of 300 to 500 ppm.…”
Section: Malavasi M De M Et Almentioning
confidence: 99%
“…Still with Passifl ora alata, Ferreira (1998) observed that GA 3 at 100 mg L -1 promoted better germination, while with Passifl ora nitida Passos et al (2004) reported that for in vitro germination the most suitable gibberellic acid concentration was 1000 mg L -1 , with or without luminosity. Botelho and Perez (2001) reported signifi cant effects on the germination percentage and speed with seeds of Peltophorum dubium Spreng (Taubert). With seeds of Jatropha elliptica, Añez et al (2006) found higher germination percentages in treatments using gibberellic acid at concentrations of 300 to 500 ppm.…”
Section: Malavasi M De M Et Almentioning
confidence: 99%
“…Seeds of P. dubium are temperature-resistent: exposition for 24 hours at 45ºC is sufficient to break the mechanical dormancy imposed by the tegument (Perez et al, 1998). Gibberellic acid allows an increase in the maximum tolerance to water stress especially in the presence of putrescin and espermidin, growth regulating substances that modulate some biological process such as cell division, responses to stressing factors and developmental processes (Botelho and Perez, 2001). Seeds of P. nitens are resistant to water stress and to several salt solutions (Nassif and Perez, 1997a).…”
Section: Tree Speciesmentioning
confidence: 99%
“…The authors recommend, in order to choose the best dose, to analyze to which market segment the product will be directed. present in the formula of Stimulate, cytokinin promotes cell division and differentiation, stimulating lateral buddings and greater leaf expansion (Reghin et al, 2000), auxin stimulates elongation and cellular differentiation of phloem and xylem, also favoring formation and development of floral organs (Davies, 2004), and gibberellin favors germination and growth by lengthening (Botelho et al, 2001).…”
Section: Introductionmentioning
confidence: 99%